PHYLOGENY AND DISJUNCTION IN ROSCOEA (ZINGIBERACEAE) - NGAMRIABSAKUL, C.; NEWMAN, M. F.; CRONK, Q. C. B. (Edinburgh Journal of Botany, 2000)
A phylogenetic study of Roscoea (Zingiberaceae), a high-altitude genus of an otherwise tropical plant family, was undertaken using sequence data from the internal transcribed spacers (ITS) of the nuclear ribosomal DNA (nrDNA). Two species of Cautleya and two species of Curcuma were used as outgroups. This resulted in an aligned matrix of 436bp (ITS1, 203bp; ITS2, 233bp). Sequence divergence of ITS1 and ITS2 within the ingroup ranged from 0–13.9% and 0–7.6% respectively. The results suggest that Roscoea is monophyletic (BS=99%; DI=>3) with the genus Cautleya as sister group. Roscoea itself is divided into two sister clades which correlate with geography: a ‘Chinese’ clade (BS=67%; DI=+2) and a ‘Himalayan’ clade (BS=59%; DI=+1). These two groups are disjunct across the ‘Brahmaputra gap’, a region in which no Roscoea spp. have been recorded. The only species which occurs on both sides of the Brahmaputra gap is Roscoea tibetica. However, the western populations of Roscoea tibetica (from Bhutan) show numerous morphological differences. It is therefore possible that Bhutanese R. tibetica represents a distinct taxon, possibly more closely allied to Himalayan species.